A Conflict Between Divine texts and Human Legal Needs? - Meiloud, Ahmed (Islamic Africa, 2016)
This paper presents excerpted translations from a longer text by the Moroccan jurist, Ahmad al-Raysuni, which highlight a key facet of contemporaneous Muslim legal debates about law and religion. They especially focus on the thorny question of whether textual sources are liable to conflict with pure rational legal considerations and hence must be sidestepped to protect personal or public interests. In these excerpts Raysuni defends his position, and that of many of the so-called ‘moderate’ Islamists, who–while decry the rigid literalism of other traditionalists—maintain that explicit textual injunctions could never conflict with rationality. They believe, as Raysuni asserts here, that any conceived contradiction between texts and rationality is either a misconception of rationality or a misunderstanding of texts.